2019
DOI: 10.1097/inf.0000000000002280
|View full text |Cite
|
Sign up to set email alerts
|

A Population-based Observational Study of Childhood Encephalitis in Children Admitted to Pediatric Intensive Care Units in England and Wales

Abstract: Sadarangani has been an investigator on research grants from Pfizer, Merck and VBI Vaccines but has received no personal payments, with all monies paid to his institution. Mrs Nickless has no disclosures. Dr Kelly receives salary support from the NIHR Oxford Biomedical Research Centre. Dr Pollard has previously conducted studies on behalf of Oxford University funded by vaccine manufacturers, but currently does not undertake industry funded clinical trials. AJP chairs the UK Department of Health's (DH) Joint Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that viral encephalitis etiology is linked to a worse prognosis, influencing patient outcomes. [19][20][21][22][23] Our study revealed nonsignificant impacts on mortality from factors such as age group, admission to the PICU, and the occurrence of status epilepticus episodes. This deviates from the findings of a previous study by Hatachi et al, which noted unfavorable outcomes associated with PICU admission within 2 days.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous studies have demonstrated that viral encephalitis etiology is linked to a worse prognosis, influencing patient outcomes. [19][20][21][22][23] Our study revealed nonsignificant impacts on mortality from factors such as age group, admission to the PICU, and the occurrence of status epilepticus episodes. This deviates from the findings of a previous study by Hatachi et al, which noted unfavorable outcomes associated with PICU admission within 2 days.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have demonstrated that viral encephalitis etiology is linked to a worse prognosis, influencing patient outcomes. 19 20 21 22 23…”
Section: Discussionmentioning
confidence: 99%
“…This is the largest study evaluating severe encephalitis in a PICU. In comparison to population-based observational studies,11 we were able to collect detailed aetiological information not only on encephalitis but also on its main differential diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of encephalitis is still substantial, with neurological impairment in over 50% of cases,9 10 and death in 10% 3 11…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 4 to 10 children per 100,000 are hospitalized with encephalitis every year (2)(3)(4) and it is associated with mortality rates of 2 to 31% (5)(6)(7). In a retrospective analysis of encephalitis cases in England and Wales in children, the annual mortality rate was 0.07 (95% CI: 0.05-0.08) per 100,000 population aged between 0-17 years (8). Amongst 7,298 children in the United States admitted with encephalitis between 2004 and 2013, 2,933 patients (40%) required treatment in a paediatric intensive care unit, and had an overall median length of hospital stay of 16 days (4).…”
Section: Introductionmentioning
confidence: 99%